1993
DOI: 10.1073/pnas.90.11.5242
|View full text |Cite
|
Sign up to set email alerts
|

Control of dorsoventral patterning of somitic derivatives by notochord and floor plate.

Abstract: We have examined the effect of implantation of a supernumerary notochord or floor plate on dorsoventral somitic organization. We show that notochord and floor plate are able to inhibit the differentiation of the dorsal somitic derivatives-i.e., axial muscles and dermis-thus converting the entire somite into cartilage, which normally arises only from its ventral part. We infer from these results that the dorsoventral patterning of somitic derivatives is controlled by sigals provided by ventral axial structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
1
6

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(151 citation statements)
references
References 23 publications
2
142
1
6
Order By: Relevance
“…Removal of the notochord at stage 10 prevents later floor plate and ventral neuronal differentiation (31), while conversely, notochord grafts (stages 10-12) placed adjacent to the neural tube induce ectopic floor plate and ventral neuron differentiation 2 days later (32). In addition, it has been shown that, in vivo, the notochord and the floor plate possess also a dorsoventral polarizing activity on the paraxial mesoderm (somites) (42). The dorsal part of the somites will segregate into the dermomyotome (which will yield the striated muscles and dermis) and the ventral part will segregate in the sclerotome (which will yield the vertebrae, the intervertebral disks, and ribs).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the notochord at stage 10 prevents later floor plate and ventral neuronal differentiation (31), while conversely, notochord grafts (stages 10-12) placed adjacent to the neural tube induce ectopic floor plate and ventral neuron differentiation 2 days later (32). In addition, it has been shown that, in vivo, the notochord and the floor plate possess also a dorsoventral polarizing activity on the paraxial mesoderm (somites) (42). The dorsal part of the somites will segregate into the dermomyotome (which will yield the striated muscles and dermis) and the ventral part will segregate in the sclerotome (which will yield the vertebrae, the intervertebral disks, and ribs).…”
Section: Discussionmentioning
confidence: 99%
“…The notochord is a midline mesodermal embryonic structure common to all members of the phylum chordata, which has essential functions in patterning the paraxial mesoderm (Herrmann et al, 1990;Dietrich et al, 1993;Pourquie et al, 1993), the neuroectoderm (van Straaten et al, 1988;Bovolenta and Dodd, 1991;Yamada et al, 1993;Placzek et al, 1993), and other tissues (Wiertz-Hoessels et al, 1987;Stern et al, 1991;Danos and Yost, 1995), through notochord-derived signals. In the zebrafish (Danio rerio), systematic mutational analysis of early development has identified several notochord-expressed genes, such as no tail (ntl) and floating head (flh) (Halpern et al, 1993;SchulteMerker et al, 1994;Talbot et al, 1995;Odenthal et al, 1996;Stemple et al, 1996;Currie and Ingham, 1996;Fouquet et al, 1997;Blagden et al, 1997;Amacher and Kimmel, 1998), in which loss-of-function mutations cause defects in the formation and/or maintenance of the notochord and within other tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In the neuroepithelium, the notochord contributes to and induces the formation of the floor plate (Placzek et al, 1993;Placzek et al, 1990;Placzek et al, 1991), and is an important inducer of motor neurons (Tanabe and Jessell, 1996). The notochord also plays a key role during sclerotomal development Brand-Saberi et al, 1993;Koseki et al, 1993;Pourquie et al, 1993), from which the bones, cartilage, and connective tissue of the axial skeleton are derived (reviewed in Christ and Wilting, 1992).…”
Section: Formation Of the Primitive Streak And The Notochordmentioning
confidence: 99%
“…Notochord ablation and transplantation experiments in the chick and analyses of mouse notochord mutants have demonstrated that the notochord participates in the specification of ventral sclerotome derivatives (BrandSaberi and Christ, 2000;Brand-Saberi et al, 1993;Dietrich et al, 1993;Goulding et al, 1993;Koseki et al, 1993;Pourquie et al, 1993). Ablation of the notochord leads to the loss of ventral sclerotome derivatives.…”
Section: From Sclerotome To Mesenchymal Prevertebraementioning
confidence: 99%